Deep defect passivation and shallow vacancy repair via an ionic silicone polymer toward highly stable inverted perovskite solar cells. Issue 10 (21st September 2022) - Wang, Tong; Li, Yuke; Cao, Qi; Yang, Jiabao; Yang, Bowen; Pu, Xingyu; Zhang, Youzi; Zhao, Junsong; Zhang, Yixin; Chen, Hui; Hagfeldt, Anders; Li, Xuanhua
Abstract : A novel ionic silicone polymer is introduced in perovskites to achieve stable inverted perovskite solar cells with high efficiency by deep defect passivation and shallow vacancy repair simultaneously. Abstract : Additive engineering is an effective strategy for defect passivation and performance improvement of perovskite solar cells (PSCs). However, few additives have achieved outstanding stability with high efficiency by simultaneously passivating deep and shallow defects. Herein, we design a novel ionic silicone polymer (PECL) with multi-active sites as an additive to modify inverted PSCs. The C–O groups in the PECL polymer can chelate with undercoordinated Pb 2+ and Pb clusters to passivate deep defects; and the ionic groups in the PECL polymer can generate electrostatic interaction with both positively and negatively charged vacancies, which help to repair shallow defects. Moreover, we quantitatively reveal the effect of deep and shallow defects on the efficiency and stability of PSCs separately, by establishing the correlation between additives with different functional groups and the performance of devices. Consequently, the power conversion efficiency of the PECL-modified inverted PSC increases from 20.02% to 23.11%. More importantly, the encapsulated PSCs maintain 95% of their initial steady-state power output after 1500 hours under AM 1.5 illumination at the maximum power point at 45 °C. Therefore, we provide a universal guideline of polymer structure design for defect healing in stabilizing PSCs with high efficiency.